Defining Control Strategies for Micro Grids Islanded Operation with Maximum Power Point Tracking using a Fuzzy Logic Control Scheme - B V Rajanna; Ganta Joga Rao; S.K Shrivastava (International Journal of Power Electronics and Drive Systems (IJPEDS), 2016)
This paper explains about an intelligent control method for the maximum power point tracking (MPPT) of a photo voltaic system with different temperature and insolation conditions. This method uses a fuzzy logic controller applied to a DC-DC converter. The different steps of the design of this controller are presented together with its simulation and the feasibility of control methods to be adopted for the operation of a micro grid when it becomes isolated. Normally, the micro grid operates in interconnected mode with the medium voltage network; however, scheduled or forced isolation can take place. In such conditions, the micro grid must have the ability to operate stably and autonomously. An evaluation of the need of storage devices and load to take off strategies is included in this paper. The MPPT of a photovoltaic system for Micro Grid operaion using a Fuzzy logic control scheme is successfully designed and simulated by using MATLAB/Simulink Software.